Ecological methods with particular reference to the study of insect populations - Southwood, T. R. E. (Chapman and Hall, 1978)
This extensive third revision of Southwood's influential Ecological Methods retains the general objectives and style of the previous editions and extends its coverage to include more up-to-date methods, such as computational techniques, distance sampling, aquatic methods and GIS. In combining both theory and pratical methods this book provides unique coverage of an area of importance to students and researchers of ecology alike.